2011
DOI: 10.2138/am.2011.3841
|View full text |Cite
|
Sign up to set email alerts
|

Argandite, Mn7(VO4)2(OH)8, the V analogue of allactite from the metamorphosed Mn ores at Pipji, Turtmann Valley, Switzerland

Abstract: Argandite, Mn 7 (VO 4 ) 2 (OH) 8 , is a new mineral from the metamorphosed synsedimentary exhalative Mn deposit located underneath the Pipji glacier (Pipjigletscher) in the Turtmann valley, Central Alps, Switzerland. The mineral is dedicated to the Swiss geologist Émile Argand . Argandite occurs in manganosite-rich ores in association with the V-minerals pyrobelonite, reppiaite, and an unknown silico-vanadate with chemical formula (Mn,Mg) 24 (V,As,Si) 4 Si 2 O 27 H 38 ; these minerals result from the remobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…O1-H1, O3-H3, O5-H5, O6-H6; Table 4). This is in line with previous studies on raadeite (Chopin et al, 2001) and argandite (Brugger et al, 2011). The principal root-meansquare components of the H-site displacement parameters obtained in this study are fairly anisotropic (as deducible from the data reported in Tables 3b,c).…”
Section: M4supporting
confidence: 92%
See 3 more Smart Citations
“…O1-H1, O3-H3, O5-H5, O6-H6; Table 4). This is in line with previous studies on raadeite (Chopin et al, 2001) and argandite (Brugger et al, 2011). The principal root-meansquare components of the H-site displacement parameters obtained in this study are fairly anisotropic (as deducible from the data reported in Tables 3b,c).…”
Section: M4supporting
confidence: 92%
“…MO 4 (OH) 2 and M2,M3,M4 MO 2 (OH) 4 ; no MO 6 unit occurs, consistent with the previous findings for raadeite (Chopin et al, 2001) and argandite (Brugger et al, 2011). The optical absorption experiment of this study confirms that the Mn valence state is 2+, and no evidence of partial substitution, with e.g.…”
Section: M1supporting
confidence: 91%
See 2 more Smart Citations
“…Strips of edge-sharing octahedra, topologically identical to those in the gatehouseite and arsenoclasite structures, are found in the structure of waterhouseite (Pring et al, 2005). Strips of edge-sharing octahedra, two octahedra wide, occur in the structures of the isotypic minerals allactite, Mn 7 (AsO 4 ) 2 (OH) 8 , (Moore, 1968), raadeite, Mg 7 (PO 4 ) 2 (OH) 8 , (Chopin et al, 2001) and argandite, Mg 7 (VO 4 ) 2 (OH) 8 , (Brugger et al, 2011).…”
Section: Structural Relationsmentioning
confidence: 99%